"Investigation of physical-spatial expansion of Shiraz metropolis using remote sensing (Rs)" - keramatollah ziari; hossein iraji (نشریه جغرافیا و برنامه‌ریزی, 2022)
Introduction As the center of the province of Fars, the City of Shiraz experienced an endogenic and organic growth until the 1960s and prior to the onset of modernity in Iran, which saw a good balance between the urban population growth rate and its area growth. Following a rise in the urban population in recent decades, the physical form of the cites also changed.Data and Method To investigate the changes and dynamism of the land cover, land use maps were developed to determine the changes over different time intervals. The maps were derived from Landsat satellite images with OLI, TM and Mss sensors in 1984 and 1994 as well as in 2014 and 2020 by using Remote Sensing techniques on the Earth Explorer Site. TerrSet software was also used to analyze the images. To analyze satellite images, it is required to use TerrSet software.Discussion and conclusionConsistent with regression model analysis, land use changes into urban territories have, over the past 40 years, involved 60% of the total area of the city of Shiraz, indicating sharp change trends in this time interval. The orientation of the changes has mainly been north to south of the city which is due to the proportionate developmental space and presence of open plains.Results Data analysis suggests that land use changes as well as their analysis in the Markov’s model are experiencing a disproportionate expansion under the effect of unsystematic and irregular urban growth. This study determines that districts 9, 10 and 6 saw an irregular (spiral) urban growth in 2018.